Local Institutional Responses to Global Market Pressures: The Sea Cucumber Trade in Yucatán, Mexico. (February 2018) - Bennett, Abigail; Basurto, Xavier
Highlights: We studied local institutional responses to the global sea cucumber trade. We conducted a comparative case study using participant observation and interviews. Relations of production shaped resource governance responses to markets. Patron–client relationships pushed open access regimes and co-ops restricted access. Sea cucumber management should emphasize fleet controls instead of quotas. Summary: The expansion of global seafood trade creates opportunities as well as risks for small-scale fisheries (SSFs) livelihoods. Markets provide economic opportunity, but without effective governance, high demand can drive resource degradation. In the context of small-scale sea cucumber fisheries in Yucatán, Mexico, this study documents local governance responses to new markets and identifies factors driving those responses. We conducted a comparative case study of two SSF communities, collecting participant observation and interview data during 16 months of fieldwork. Our study found that local rules-in-use did not match government regulations and that the emergence of local rules was shaped by relations of production in each study site. Specifically, patron–client relationships promoted an open access regime that expanded local fishing fleets while fishing cooperatives attempted to restrict access to local fishing grounds through collective action and multi-level linkages with government. We propose that the different material incentives arising from the way that patron–client relationships and cooperatives organize labor, capital, and profits help explain these divergent governance responses. We hypothesize that this finding is generalizable beyond the study context, especially given that patron–client relationships and cooperatives are common throughout the world's SSFs. This finding builds on previous research that indicates local institutions can mediate the effects of market pressures, showing that the emergence of local rules depends on how resource users are organized not just in relation to resource governance but vis-à-vis the markets themselves. Therefore, effective policies for SSFs facing market pressures require a greater emphasis on regulating local-level trade and governing the commercial aspects of fishing livelihoods. These lessons are relevant to the estimated 540 million individuals whose livelihoods SSFs support who may increasingly engage in the global seafood trade.